2008
DOI: 10.1038/nature07517
|View full text |Cite
|
Sign up to set email alerts
|

Accurate whole human genome sequencing using reversible terminator chemistry

Abstract: DNA sequence information underpins genetic research, enabling discoveries of important biological or medical benefit. Sequencing projects have traditionally employed long (400–800 bp) reads, but the existence of reference sequences for the human and many other genomes makes it possible to develop new, fast approaches to re-sequencing, whereby shorter reads are compared to a reference to identify intra-species genetic variation. We report an approach that generates several billion bases of accurate nucleotide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
2,597
6
26

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,127 publications
(2,675 citation statements)
references
References 33 publications
46
2,597
6
26
Order By: Relevance
“…There are currently three routinely used platforms for MPS: the Roche 454 system[58], the Illumina HiSeq[59], and the SOLiD system of Applied Biosystems[60]. A fourth, the PacBio RS single molecule sequencing system of Pacific Biosciences[61], was introduced fairly recently and will be briefly discussed later.…”
Section: Massively Parallel Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently three routinely used platforms for MPS: the Roche 454 system[58], the Illumina HiSeq[59], and the SOLiD system of Applied Biosystems[60]. A fourth, the PacBio RS single molecule sequencing system of Pacific Biosciences[61], was introduced fairly recently and will be briefly discussed later.…”
Section: Massively Parallel Sequencingmentioning
confidence: 99%
“…The two major alignment algorithms used are hash table–based algorithms (BLAST, MAQ[68], Eland[59]) and Burrows Wheeler transform (BWT)-based methods (SOAP2[69], BWA[70], Bowtie[71]). Hash table-based algorithms use an indexing scheme that enables ultra-fast searches for short sequences of a defined length k (k-mer matches or seeds) with up to m mismatches.…”
Section: Massively Parallel Sequencingmentioning
confidence: 99%
“…Another commonly used approach is to apply quality filters that are aimed at selectively removing errors. Every whole-genome sequence reported so far has used filtering to some extent: the most commonly used filters being those that remove sequences with a too-low coverage depth, discard variants with a low-confidence score or eliminate variants located within a cluster of variants 3,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Surprisingly, there is little consensus with respect to which filters should be used and at which threshold they should be applied.…”
mentioning
confidence: 99%
“…So far, seven human diploid genomes have been fully sequenced, and some important insights have been gained from these resequencing studies. [145][146][147][148][149][150][151] The most prominent finding from these studies is that, besides SNPs, other genetic variants are also abundant in the human genome. These studies found that in addition to the 3-4 million SNPs, several hundred-thousand of short indels (for example, sizes defined as 3 and 16 bp or less in the Bentley et al 147 and Wang et al 148 study, respectively) are also present in each individual human genome.…”
Section: Human Genetic Variationmentioning
confidence: 99%